Effect of rigid boundary on Rayleigh wave in an incompressible heterogeneous medium over an incompressible half-space - Kumar Mukhopadhyay, Anup; Kumar Gupta, Asit; Kundu, Santimoy; Patra, Pulak (AIMS mathematics, 2020)
In the present problem, an attempt has been made to study the propagation of Rayleigh waves in an incompressible medium with polynomial variation (m) of rigidity over an incompressible half-space under rigid layer. Instead of using the Whittaker function, the expansion formula proposed by Newlands has been used for a better result in shallow depth. The velocity equation has been calculated and the results are shown in figures. The study in the assumed medium, the authors obtained that the phase velocity of Rayleigh waves increases except for the polynomial variation of rigidity m=1, 2 and 3.